ANALYSIS OF THE COMPETITIVE STRATEGY OF PERCAYA DIRI TOFU FACTORY IN UTAN JAYA VILLAGE, CIPAYUNG DISTRICT, DEPOK CITY - Mujito Mujito; Tika Kartika Asri; Eidelweijs Andririnjani Putri (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the internal and external business environment and determine the priority competitive strategy for the Percaya Diri Tofu Factory located in Utan Jaya Village, Cipayung District, Depok City. A descriptive qualitative approach was employed using SWOT analysis as the analytical tool. The findings reveal that the company's main strength is its strong customer relationships (score 0.51), while its primary weakness is the absence of a flagship product (score 0.42). The main opportunities include a broad market share and high customer loyalty (score 0.46), whereas the major threats are intense competition and fluctuating raw material prices (score 0.22). Based on the IFE, EFE, and SWOT analyses, the recommended strategy is business development to enhance the company's competitive advantage.